Report of a case involving novel use of a post-operative esophagogastroduodenoscopy to re-evaluate a duodenal ulcer bleed. (2020) - DeVito, Robert; Shoukry, Sameh; Arif, Azzan; Fullmer, Rhett; Simpson, Matthew; Kimyaghalam, Ali
Highlights: Acute duodenal ulcer bleeds can be life-threatening. The best initial management is by endoscopy or Interventional Radiology. Emergency surgical intervention is indicated if unable to control. Post-surgical endoscopy in an OR setting was used to re-evaluate. May be a viable option for post-surgical re-evaluation in the absence of IR. Abstract: Introduction: Acute gastrointestinal (GI) bleeding can be a life-threatening condition. This is usually diagnosed and managed by an upper GI tract endoscopy. When treating actively bleeding duodenal ulcers, surgical intervention, or arterial embolization by Interventional Radiology (IR) is warranted in the event of failed initial management. We present a patient with a significant GI bleed and failure of management through endoscopy, necessitating emergent surgical intervention. Presentation of case: An 87-year-old female presented to the emergency department after a fall. Her hemoglobin level dropped significantly and an esophagogastroduodenoscopy (EGD) revealed a large pool of blood in the stomach but had a limited view of an active bleed. The patient was taken emergently to the operating room (OR) where she underwent an exploratory laparotomy, gastroduodenostomy, suture ligation, and pyloroplasty. The following day, she had increased sanguineous output from her nasogastric (NG) tube. Re-evaluation was done with an EGD in the OR. The patient tolerated all procedures well and was transferred to a facility with IR capabilities for further management. Discussion: An EGD hours after gastroduodenostomy runs a high risk for perforation and is not the typical course of action. Given the lack of IR availability and concern for rebleeding, this procedure was performed in the OR to minimize risk. Conclusion: A favorable outcome was achieved with this patient and hemostasis was confirmed with the post-operative EGD. Further studies will determine whether this approach is a viable option for facilities without IR until the patient can be transferred.